Anticonvulsant activity of leaf extracts of Martynia annua linn in experimental rats - Neeti Srivastav; Sarla Saklani; Vijay Juyal; Brijesh K Tiwari (International Journal of Phytomedicine, 2014)
Martynia annua Linn (Martyniaceae) is a medicinal herb used for the treatment of epilepsy in the traditional health care system of Uttarakhand (India). The present study reports the anticonvulsant activities in the ethanolic and aqueous extracts of the leaves of Martynia annua Linn on the rats, induced both chemically and electrically. The models chosen for the activity were Maximal Electroshock (MES) and Pentylenetetrazole (PTZ) induced convulsions in rats. The test dose studied were 200 and 400 mg/kg body weight orally of ethanolic and aqueous extracts of Martynia annua. Acute toxicity studies of the extract shows that the extract was non toxic up to the recommended dose 2000mg/kg body weight orally as per OECD guideline no 423. In PTZ induced seizures, onset of clonic convulsions were studied while in MES model reduction in mean duration of extensor phase was noted. Both aqueous and ethanolic extracts showed anticonvulsant activities against MES and PTZ animal models.